2012
DOI: 10.1007/s00435-012-0170-3
|View full text |Cite
|
Sign up to set email alerts
|

Palatal and lingual adaptations for frugivory and nectarivory in the Wahlberg’s epauletted fruit bat (Epomophorus wahlbergi)

Abstract: Wahlberg's epauletted fruit bat (Epomophorus wahlbergi) feed on fleshy fruit and nectar of flowers and have an important role in pollination and seed dispersal. It was expected that their buccal morphological structures are adapted to this type of feeding. Consequently, buccal cavity and lingual structures of E. wahlbergi were examined by extended focus light microscopy (LM) and scanning electron microscopy (SEM). Morphology of the tongue of E. wahlbergi was similar to that of other fruitand nectar-feeding bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 32 publications
9
20
0
Order By: Relevance
“…Our study in Egyptian fruit bat agrees with that noted in the previous articles (Emuraet al, 2001b;Mqokeli & Downs;Birt et al;Kobayashi & Shimamura, 1982, EmuraHayakawa et al, 2002b, that the giant trifid filiform papilla are common in all bat species, but (Greenbaum and Phillips, 1974) in two species of bats (flower-eating), added that there are also two large, bifid, horny papillae located next to each other along the midline of the tongue, and also (Ghassemi & Jahromi;Jackowiak et al, 2009) noted that there are bifid Filiform Papillae and described as they are similar to giant type but had bifid ends and oriented to the lateroposterior of tongue, moreover (Park & Hall) made comparative studies of the tongue in a total of three families and eight species, nectar-eating, fruit-eating, and vampire bats, and reported that there are large bifid papillae were distributed on the posterior middle area of the tongues of fruiteating bat (Macrotus and Artibeus), while out distributed near the tongue tip in all bats. Whouber, the trifid and bifid filiform papillae were abscent in; molossid bats (Gregorin), common European bat (Pastor et al, 1993), hematophagous bats (Masuko et al).…”
Section: Discussionsupporting
confidence: 93%
“…Our study in Egyptian fruit bat agrees with that noted in the previous articles (Emuraet al, 2001b;Mqokeli & Downs;Birt et al;Kobayashi & Shimamura, 1982, EmuraHayakawa et al, 2002b, that the giant trifid filiform papilla are common in all bat species, but (Greenbaum and Phillips, 1974) in two species of bats (flower-eating), added that there are also two large, bifid, horny papillae located next to each other along the midline of the tongue, and also (Ghassemi & Jahromi;Jackowiak et al, 2009) noted that there are bifid Filiform Papillae and described as they are similar to giant type but had bifid ends and oriented to the lateroposterior of tongue, moreover (Park & Hall) made comparative studies of the tongue in a total of three families and eight species, nectar-eating, fruit-eating, and vampire bats, and reported that there are large bifid papillae were distributed on the posterior middle area of the tongues of fruiteating bat (Macrotus and Artibeus), while out distributed near the tongue tip in all bats. Whouber, the trifid and bifid filiform papillae were abscent in; molossid bats (Gregorin), common European bat (Pastor et al, 1993), hematophagous bats (Masuko et al).…”
Section: Discussionsupporting
confidence: 93%
“…Gross anatomy observation of the tongue R. amplexicaudatus was characterized by elongated tongue with round long free anterior part. This shape is used to facilitating the movement of tongue while swiping the extracts of the fruit (Abumandour & El‐Bakary, ; Birt, Leslie, & Geoffrey, ; Mqokeli & Downs, ). The tongue was divided into three regions: the apex, the corpus and the radix (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our finding, the lingual median sulcus is a characteristic feature in some mammals: Clethrinomys glareolus and Hemiechinus auritus (Jackowiak & Godynicki, ; Nasr, Gamal, & Elsheikh, ). In contrast, this groove is absent in some mammalian species: Cynopterus brachyotis , R. aegyptiacus and Epomophorus wahlbergi (Emura et al (), Jackowiak et al (), Mqokeli and Downs (), and Abumandour and El‐Bakary ()). Meanwhile, the characteristic feature of the dorsal surface of middle part was the presence of the lingual prominence which was located close to the posterior half area of the tongue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(), Jackowiak et al. (), Mqokeli and Downs (), and Abumandour and El‐Bakary (). The present investigation observed that there is a slightly median elevated ridge in the median region of the anterior and middle parts of the tongue.…”
Section: Discussionmentioning
confidence: 99%